Occupational Choice and the Process of Development - Banerjee, Abhijit V.; Newman, Andrew F. (Journal of Political Economy, 1993)
This paper models economic development as a process of institutional transformation by focusing on the interplay between agents' occupational decisions and the distribution of wealth. Because of capital market imperfections, poor agents choose working for a wage over self-employment, and wealthy agents become entrepreneurs who monitor workers. Only with sufficient inequality, however, will there be employment contracts; otherwise, there is either subsistence or self-employment. Thus, in static equilibrium, the occupational structure depends on distribution. Since the latter is itself endogenous, we demonstrate the robustness of this result by extending the model dynamically and studying examples in which initial wealth distributions have long-run effects. In one case the economy develops either widespread cottage industry (self-employment) or factory production (employment contracts), depending on the initial distribution; in the other example, it develops into prosperity or stagnation.